2017
DOI: 10.1186/s12934-017-0740-7
|View full text |Cite
|
Sign up to set email alerts
|

Reversible bacterial immobilization based on the salt-dependent adhesion of the bacterionanofiber protein AtaA

Abstract: Background: Immobilization of microbial cells is an important strategy for the efficient use of whole-cell catalysts because it simplifies product separation, enables the cell concentration to be increased, stabilizes enzymatic activity, and permits repeated or continuous biocatalyst use. However, conventional immobilization methods have practical limitations, such as limited mass transfer in the inner part of a gel, gel fragility, cell leakage from the support matrix, and adverse effects on cell viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…This feature is hardly realized in direct immobilization through biofilm formation. The immobilized-cells by AtaA are hardly detached in buffer solution, while they are easily detached in pure water [33]. In this study, the results shown in Figure 5 suggest that the cells on polyurethane were maintained during the continuous reaction over 30 h without leaching, because the reaction rate did not reduce.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…This feature is hardly realized in direct immobilization through biofilm formation. The immobilized-cells by AtaA are hardly detached in buffer solution, while they are easily detached in pure water [33]. In this study, the results shown in Figure 5 suggest that the cells on polyurethane were maintained during the continuous reaction over 30 h without leaching, because the reaction rate did not reduce.…”
Section: Discussionmentioning
confidence: 58%
“…Overexpression of membrane proteins such as AtaA is commonly considered to become toxic, because the excessively produced proteins disrupt the bacterial membrane structures [34][35][36]. In our previous report, we unexpectedly found that immobilization of bacteria by surface production of AtaA causes no damage to the cells [33]. Moreover, the over expression of ataA did not seem to affect severely on E. aerogenes's growth.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…AtaA mediates the nonspecific, high adhesiveness to various abiotic surfaces mentioned above. This adhesive property can be conferred to originally non-adhesive bacteria by transformation with ataA and are applicable to cell immobilization in bioprocesses 24 26 . However, the behavior of Tol 5 cells in flows under the effect of shear stress has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%